The Influence of Project Based Learning and Motivation Achievement on Improving Writing Ability - Hanafi, Hanafi (Universitas Muhammadiyah Jember, 2017)
Writing skill is one of the English skills which is often regarded as somethingdifficult to master. Students tend to have less attention to this skill. Even worse,some teachers also often lack of attention to it since it requires more time to checkthe students work on writing. Consequently, the students’ writing competenceis difficult to increase. To overcome the problem, the possible alternative theteacher can use is using Project Based Learning since the approach seems to beeffective to improve the students’ writing competence. The other aspect that can possibly influence the writing competence is Motivation Achievement. In this research, the problem investigated is whether or not there is influence usingProject Based Learning and Achievement Motivation in increasing writingability. The kind of research used is experimental research with nonrandomizedcontrol group pretest posttest design. The data analysis used is t-test usingSPSS version 21. The result of the research shows that Project Based Learninginfluences the students’ writing ability, while Achievement Motivation has nosignificant impact on the students’ writing ability.